PERSEPSI WISATAWAN NUSANTARA TERHADAP KONDISI KEPARIWISATAAN BALI - I Made Kusuma Negara (Institut Pariwisata dan Bisnis Internasional, 2012)
Bali is the common destination for foreign traveller as well as domestic traveller. The number of domestic traveller gives the economic impact for each country and multiplier effect. Therefore, the domestic traveller has the essence to analyse for this research. The purposes of this research are: (1) to analyse the perception of domestic traveller related to the tourism circumstances in Bali; (2) and to analyse the correlation between the social economic and demography of the domestic traveller’s variable with the own perception related to the tourism circumstances in Bali.In order to achieve the purpose of this research, sampling is done located at departure gate in Ngurah Rai Airport by using domestic traveller’s departure from Bali as respondent. Respondent is done by non-probability sampling method and direct questionnaire to be fulfilled by domestic traveller. There are 150 respondents that used to interview by accidental sampling method. There are two variables that are used to analyse the tourism circumstance in Bali that are physics and service. Some approaches are used in analysing data, which are to analyse the traveller’s perception domestic related to the tourism circumstances in Bali by descriptive aspect and to analyse the correlation between the social economic and demography of domestic traveller’s variable with the own perception related to the tourism circumstances in Bali by chi-square method.Based on the result analyses, there are six variables of adequate perception from seventeen variables of the tourism circumstance in Bali, i.e. the cleanliness of public area, the cleanliness of tourist object, the quality of transportation, reasonable price, reasonable quality of services and the quality of servicing trader, while the other variables gets better perception. The correlation between the social economy and demography of the domestic traveller’s variable with the own perception related to the tourism circumstances in Bali gets insignificant correlation, except the residence of the domestic traveller’s variable. Refer to the analysing result; it is important to optimize the cleanliness of public facilities, cleanliness at tourist attraction, quality of transportation facilities, and quality of services.